POETIC FEATURES OF AMERICAN GOTHIC WORKS OF THE XX-XXI CENTURIES (International Conference on Education, Psychology and Humanities, 2026)
This article examines the principal poetic features that define American Gothic literature from the twentieth century to the present day. Drawing on established scholarly frameworks by David Punter, Leslie Fiedler, Teresa Goddu, and Allan Lloyd-Smith, the study identifies key narrative strategies including the uncanny doubling of characters, the symbolic encoding of national trauma, spatial liminality, and the subversion of domestic space that distinguish American Gothic from its European predecessor. Particular attention is given to how contemporary authors such as Toni Morrison, Cormac McCarthy, Shirley Jackson, and Carmen Maria Machado have expanded the genre’s poetic repertoire through polyphonic narration, unreliable focalization, and the aestheticization of bodily horror. The article concludes that the enduring vitality of American Gothic lies in its capacity to transform collective anxieties into compelling literary form.
Keywords: American Gothic, poetic features, uncanny, narrative strategies, spatial liminality, national trauma, contemporary fiction.